The right parasternal window: when Doppler-beam alignment may be life-saving in patients with aortic valve stenosis. Issue 10 (October 2020) - Benfari, Giovanni; Mantovani, Francesca; Romero-Brufau, Santiago; Setti, Martina; Rossi, Andrea; Ribichini, Flavio L.; Nistri, Stefano; Clavel, Marie-Annick
Abstract : N/A: The need for multiple transducer positions, especially from right parasternal windows, is consistently mentioned in the recommendations for the accurate measurement of peak velocities across a stenotic aortic valve, but yet poorly adopted. We performed a subanalysis of the largest prospective series on the right parasternal acoustic windows in patients with aortic stenosis (330 consecutive) to calculate the degree of misalignment and estimate the potential outcome implication of this often-forgotten approach. The right parasternal view was highly feasible with an average estimated misalignment from the apical view of 14 ± 16 degree; in 10 cases, an estimated misalignment >40 degree. Right parasternal assessment (vs. apical alone) provided a significant reclassification from moderate to severe or even very-severe aortic valve stenosis. Considering a wellestablished survival benefit provided by either percutaneous or surgical valve replacement in patients with severe aortic stenosis the reclassification would result in approximately 1 life-year saved for every 30–35 patients in whom parasternal view were effectively utilized. Abstract : Supplemental Digital Content is available in the text